A Study of Creep Behavior of TSV-Cu Based on Nanoindentaion Creep Test. (5th August 2016) - Wu, W.; Qin, F.; An, T.; Chen, P.
Abstract : Through-Silicon-Via (TSV) is considered to be the most potential solution for 3D electronic packaging, and the mechanical properties of TSV-Cu are critical for TSV reliability improving. In this paper, to make deeply understand the creep behavior of TSV-Cu, nanoindentation creep tests were conducted to obtain its creep parameters. At first, the TSV specimens were fabricated by means of a typical TSV manufacturing process. Then a combination programmable procedure of the constant indentation strain rate method and the constant load method was employed to study the creep behavior of TSV-Cu. To understand the influence of the previous loading schemes, including the different values of the indentation strain and the maximum depths, the nanoindentation creep tests under different loading conditions were conducted. The values of creep strain rate sensitivity m were derived from the corresponding displacement-holding time curves, and the mean value of m finally determined was 0.0149. The value of m is considered no obvious correlation with the different indentation strain rates and the maximum depths by this method. Furthermore, the mechanism for the room temperature creep was also discussed, and the grain boundaries might play an significant role in this creep behavior.